INVOLVEMENT OF CHILDREN WITH DISABILITIES INTO INCLUSIVE EDUCATION (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article deals with the involvement of children with disabilities in inclusive education and its ways. The content, essence of inclusive education and the types of children with special educational needs who are involved in inclusive education are presented.